Spindle Cell Carcinoma of the hypopharynx: a case report - Kandel, Dillu Ram (Journal of College of Medical Sciences-Nepal, 2018)
Spindle cell carcinoma of hpopharynx is a rare pathology. It is a poorly differentiated variant of squamous cell carcinoma and morphologically resembles sarcoma. This is a disease of old age. It is usually associated with smoking and alcohol abuse. When it is associated with radiation exposure history it behaves more aggressively. Surgery is considered as the main modality of treatment and adjuvant radiotherapy if necessary. Here we present a case of 79 year old male with spindle cell carcinomaof right piriform fossa with 2-month history of progressive dysphasia and hoarseness that has been affecting his ability to speak and swallow with history of weight loss and past history of radiotherapy. So possibility of spindle cell carcinoma of the hypopharynx should beconsidered in an old patient with rapidly developing swelling of the hypopharynx with past history of radiation exposure. As it is a highly aggressive disease it should be treated timely and more aggressively to prolong the survival of the patient.